Odpowiedź :
1)
[tex]2\frac{3}{8}+1\frac{1}{6}=2\frac{3\cdot3}{8\cdot3}+1\frac{1\cdot4}{6\cdot4}=2\frac{9}{24}+1\frac{4}{24}=3\frac{13}{24}\\[/tex]
2)
[tex]4\frac{1}{2}+2\frac{3}{5}=4\frac{1\cdot5}{2\cdot5}+2\frac{3\cdot2}{5\cdot2}=4\frac{5}{10}+2\frac{6}{10}=6\frac{11}{10}=7\frac{1}{10}\\[/tex]
3)
[tex]4\frac{1}{4}-2\frac{2}{3}=4\frac{1\cdot3}{4\cdot3}-2\frac{2\cdot4}{3\cdot4}=4\frac{3}{12}-2\frac{8}{12}=3\frac{15}{12}-2\frac{8}{12}=1\frac{7}{12}\\[/tex]
4)
[tex]5\frac{1}{9}-1\frac{5}{6}=5\frac{1\cdot2}{9\cdot2}-1\frac{5\cdot3}{6\cdot3}=5\frac{2}{18}-1\frac{15}{18}=4\frac{20}{18}-1\frac{15}{18}=3\frac{5}{18}\\[/tex]
5)
[tex]3\frac{1}{15}-1\frac{1}{10}=3\frac{1\cdot2}{15\cdot2}-1\frac{1\cdot3}{10\cdot3}=3\frac{2}{30}-1\frac{3}{30}=2\frac{32}{30}-1\frac{3}{30}=1\frac{29}{30}\\[/tex]
6)
[tex]5\frac{5}{13}-3\frac{1}{2}=5\frac{5\cdot2}{13\cdot2}-3\frac{1\cdot13}{2\cdot13}=5\frac{10}{26}-3\frac{13}{26}=4\frac{36}{26}-3\frac{13}{26}=1\frac{23}{26}\\[/tex]